Experience of First-Time Mothers in Caring for Premature Babies at Imelda Indonesian Workers Hospital Medan in 2025 - Risatantry Gultom; Ervina Agustin; Agus Mutiara Situmeang; Siti Nurjannah Pasaribu; Silpianna Pane (Cattleya Darmaya Fortuna, 2026)
Background: Premature birth is a significant global and national health issue causing substantial psychological distress in primiparous mothers. Their lack of experience and the challenging NICU environment exacerbate maternal anxiety and self-distrust. This study aims to explore the experiences of primiparous mothers in caring for premature infants at Imelda Pekerja Indonesia Hospital, Medan. Objective: To explore the experiences of primiparous mothers in caring for premature infants at Imelda Pekerja Indonesia Hospital, Medan, including their level of knowledge and readiness, pregnancy and delivery history, psychological status, and family and healthcare professional support. Methods: A descriptive qualitative study with a phenomenological approach was employed. A sample of 7 primiparous mothers was selected through purposive sampling. Data were collected via semi-structured interviews and analyzed thematically. Validity was maintained through member checking and source triangulation. Results: Five main themes and thirteen subthemes were identified: (1) Mother's Knowledge and Readiness Level (lack of knowledge, readiness to care, care practices, role transformation); (2) Pregnancy and Delivery History (ANC non-compliance, complications, signs of prematurity); (3) Psychological Status (psychological changes, coping mechanisms); (4) Support (family, husband, healthcare professionals); and (5) Mother's Hopes (healthy baby). Primiparous mothers faced significant challenges but demonstrated strong adaptation due to comprehensive support. Conclusion: Primiparous mothers experience emotional and knowledge complexities in caring for premature infants but show resilience and adaptation. Support from family, husbands, and healthcare professionals is crucial in this process, shaping hopes for the baby's optimal health. Recommendations include enhancing education, psychosocial support, and a more supportive care environment.